La importancia de los bienes públicos en la calidad de vida local: El caso de Manizales, Colombia - Liliana Velasquez (Inter-American Development Bank (IDB), 2011)
– This paper applies a method designed by the BID to monitor of urban quality based on the combination of two approaches: hedonic prices and lifestile satisfaction. This combination allows the assessment of local public resources from both the market point of view and that of profitability. Unlike other monitoring systems, this one focuses on few dimensions (those related to the occupancy of the urban surroundings) and offers valuable information for the design and prioritization of public policies. The results of the application of the method for the city of Manizales, Colombia, reveal that, although for some public resources the assessment carried out by the market is suitable, for others there is an additional assessment represented in the well-being passed on to the inhabitants and which the market does not manage to capture.
Keywords: D60; H41; R28; 330